Rural population mixing and childhood leukaemia: effects of the North Sea oil industry in Scotland, including the area near Dounreay nuclear site. Issue 6880 (20th March 1993) - Kinlen, L J; O'Brien, F; Clarke, K; Balkwill, A; Matthews, F
Abstract : OBJECTIVE–To determine if any excess of childhood leukaemia and non-Hodgkin's lymphoma was associated with certain striking examples of population mixing in rural Scotland produced by the North Sea oil industry. DESIGN–Details were traced for over 30, 000 workers involved in the construction of the large oil terminals in the Shetland and Orkney islands in northern Scotland or employed offshore. Home addresses of the 17, 160 Scottish residents were postcoded, integrated with census data, and then classified as urban or rural. Rural postcode sectors, ranked by proportion of oil workers, were grouped into three categories with similar numbers of children but contrasting densities of oil workers. The incidence of leukaemia and non-Hodgkin's lymphoma was examined in these rural (and also in urban) categories in the periods 1974-8, 1979-83 and 1984-8. SETTING–Scotland. SUBJECTS–Young people below age 25. RESULTS–A significant excess of leukaemia and non-Hodgkin's lymphoma was found in 1979-83 in the group of rural home areas with the largest proportion of oil workers, following closely on large increases in the workforce. The area near the Dounreay nuclear installation, where an excess of leukaemia is already well known, was within the rural high oil category. CONCLUSION–The findings support the infection hypothesis that population mixing can increase the incidence of childhood leukaemia in rural areas. They also suggest that the recent excess in the Dounreay-Thurso area is due to population mixing linked to the oil industry, promoted by certain unusual local demographic factors.